Differences in the Nasal Inflammatory Response to Cynodon dactylon From Rural and Urban Areas in Patients With Allergic Rhinitis - Sánchez, Jorge; Sánchez, Andres; Sánchez, Jorge (Allergy & rhinology (Providence, R.I.), 2018)
Background Epidemiological and experimental studies suggest that air pollution has a negative impact on human health and modifies the environment. However, the clinical implications of changes in environmental allergens secondary to air pollution have been little studied. Objectives To explore if the growth conditions of the Cynodon dactylon (rural vs urban area) modify the inflammatory response among patients with allergic rhinitis. Methodology: Two extracts were prepared for diagnostic test with Cyn d proteins obtained from rural and urban environment. Skin prick test (SPT), nasal challenge test (NCT), and eosinophil count in nasal mucus were performed in 3 groups: healthy subjects without rhinitis, rhinitis with (+) Cyn d, and rhinitis with (−) Cyn d. Results There was a 97% concordance in the positive and negative results of the SPT with the 2 extracts. However, Cyn d-urban extract generated larger wheals (P = .03) and a higher number of patients with rhinitis presented a positive NCT to this extract (n = 7 vs 14, P = .04). Patients with positive NCT had a significant increase in eosinophils in mucus, but there was no difference between the extracts. The healthy controls did not react to the extracts tested in the skin or nasal test. Conclusion The findings suggest that the growth conditions in urban area of Cynodon dactylon can generate changes in the protein extract and have clinical implications in patients with allergic rhinitis.